Physiotherapy graduates' contribution to South Africa's health needs - A ten year survey of the University of the Witwatersrand - A. Stewart (South African Journal of Physiotherapy, 1994)
Graduates of the University of the Witwatersrand Physiotherapy department were surveyed by means of a questionnaire over a ten-year period, 1980-1990. It was found that almost thirty percent of the graduates were not in any way contributing to the health needs of the country. Twenty percent have left the country and a further nine percent are not practising physiotherapists. Of the remainder, only twenty-six percent are working in the public health sector which serves eighty percent of the population. Their work profiles and job satisfaction are also discussed.